Health Implications of Domestic Wastewater Treatment Through Biofilter Technology: A Review - Rezki Aulia; Nur Indriyani; Melna puspita Sari; Zahratun Nisa (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Domestic wastewater management plays a crucial role in environmental conservation and improving public health. In areas with limited access to centralized treatment networks, biofilter technology can be an effective, affordable, and sustainable solution for managing household wastewater. Objectives: The purpose of this literature review is to examine and combine the latest findings related to the application, level of effectiveness, and various determining factors of the performance of biofilter technology in treating domestic wastewater. Method: This study uses a systematic literature review method by analyzing 25 related national and international journals from Google Scholar published between 2020-2025. Results: Based on the analysis results, biofilter technology, especially the anaerobic-aerobic system and the Moving Bed Biofilm Reactor (MBBR), has been proven to be able to reduce the concentration of major pollutant parameters with high consistency. Data shows the efficiency of reducing Biochemical Oxygen Demand (BOD) reaching 89%, Chemical Oxygen Demand (COD) 87% and Total Suspended Solids (TSS) up to 96%. The performance of this system is increasingly optimal when combined with supporting technologies such as filtration and phytoremediation (hybrid systems). Several determining factors for successful implementation include the type of filter media used, operational conditions (pH, temperature, and flow rate), and active community involvement. Conclusion: Wastewater treatment, both from households and industries, is rapidly evolving with the use of technologies such as anaerobic-aerobic biofilters, combining AOP with biological processes, vermifiltration, and the reuse of treated water for irrigation and green spaces. These technologies can meet environmental standards and support sustainability, cost efficiency, and resource conservation. While challenges remain, continued innovation in this area points to a brighter and more environmentally friendly future in wastewater management. Keywords: Biofilms, biological oxygen, bioreactors, oxygen, hidrogen-ion concentration